Optimalisasi Limbah Kulit Buah Nanas, Jeruk, Dan Buah Naga Sebagai Bahan Baku Pembuatan Pupuk Organik Cair - Muhammad Faiqul Azmi; Muhammad Fikri Fakhruddin; Rifqi Nabil Fawwaz; Denny Oktavina Radianto (KOLONI, 2024)
Indonesia is an agricultural country where many of the crops grown can be utilized. In everyday life, one of the main human needs is food. So, to fulfill their needs, humans need to consume food, one of which is fruit. There are many benefits for the human body's vitamin needs. However, sometimes many people think that there are some parts of the fruit that cannot be used. Usually this part is the skin, even though if it is innovated the fruit skin still has a lot of content that can be utilized. Therefore, researchers use waste from fruit peels to be used as liquid organic fertilizer. The research method used is experimentation with data obtained from digital, scientific journals and the internet. The results obtained are organic fertilizers whose quality is compared with fertilizers on the market by testing the quality and temperature of organic fertilizers